Epidemiology and Elimination of HCV-Related Liver Disease - Pradat, Pierre (Viruses, 2018)
Hepatitis C virus (HCV) infection, defined by active carriage of HCV RNA, affects nearly 1.0% of the worldwide population. The main risk factors include unsafe injection drug use and iatrogenic infections. Chronic HCV infection can promote liver damage, cirrhosis and hepatocellular carcinoma (HCC) in affected individuals. The advent of new second-generation, direct-acting antiviral (DAA) agents allow a virological cure in more than 90% of treated patients, and therefore prevent HCV-related complications. Recently, concerns have been raised regarding the safety of DAA-regimens in cirrhotic patients with respect to the occurrence and the recurrence of HCC. Here, we review the current available data on HCV epidemiology, the beneficial effects of therapy, and discuss the recent controversy with respect to the potential link with liver cancer. We also highlight the challenges that have to be overcome to achieve the ambitious World Health Organization objective of HCV eradication by 2030.